Скотарська тематика Великодніх свят у волинян - Пожоджук, Д. Д. (My University, 2019)
In the publication there is analyzed a cattle-breeding aspect of the Easter holidays of Volyn’ folk calendar. There are described cattle-breeding customs and rites that existed during the days of the Easter period at the end of the 19th – beginning of the 21st century. The place of a witch in the rituals of the Easter holidays is described from the cattle farmers’ point of view. There are represented examples of ritual feeding of domestic animals with the blessed products from the Easter basket. In particular, the in article there is described about the pieces of paska and ritual bread that was baked specially for the cattle. The focus is made on the period of the Easter holidays as a favourable time for the first ritual grazing of the cattle. The article is written on the basis of field ethnographic materials.
Cattle-Breeding Theme of the Easter Holidays Among Volyn’ Inhabitants
Keywords: етнологія; історико-етнографічна Волинь; ethnology; ethnographic Volyn’